Settlement of Productive Waqf Disputes from the Perspective of Law Number 41 of 2004 on Waqf - Mubarak, Farisul Islam (Sakina: Journal of Family Studies, 2025)
Waqf as a solution to achieve the economic stability of the ummah certainly aims to gain benefits. Waqf is inseparable from the potential for disputes that will actually reverse the purpose of waqf from benefit to the emergence of harm. One of the disputes arising from this is the dispute over productive waqf in the form of rice fields in Panyampa Village, Campalagian District. The rice field was endowed by the As-Salafi Foundation as a productive waqf. As a result of the lack of proof of ownership of the rice field by the previous owner, a dispute arose with a claim from another person over the rice field. This research was conducted with the aim of providing understanding and raising awareness to the community, especially in Campalagian District, of the importance of paying attention to the management and management of waqf assets. The method used in this research is empirical research with a qualitative approach. The research was conducted by conducting semi-structured interviews with several informants related to waqf assets. The results showed that the dispute occurred due to a claim from the family of the original owner of the rice field, more precisely Puang Hasan’s brother-in-law. The settlement was carried out by mediation without going through the deliberation process. The mediation was conducted by the Police, because the Religious Affairs Office felt that it did not have the responsibility to resolve waqf disputes. The settlement of productive waqf disputes in Panyampa Village is in accordance with the provisions of Law No. 41/2004 on Waqf.